Perancangan Model Aplikasi Pemesanan Tiket Travel berbasis Android Studio - Adil Setiawan; Dedek Indra Gunawan Hts; Rita Novita Sari (LPPM Universitas Al Washliyah Labuhanbatu, 2022)
In this day and age, many people or companies are competing to create something that is very useful for human life in everyday life. for example, create a Travel application. Many people who carry out daily activities such as going to work complain that it is difficult to find transportation such as angkot, taxi, or bus. While their position is in a grace period or in a hurry to go to work. This is where brilliant ideas emerge that are made by people or companies to make people's lives easier. This idea arose from direct observation in the field, which would make something that was initially difficult to be simple. The idea is to create an android-based travel application. This travel application will help many people go to work, vacation, or find lodging without having to go to their place or compete with other people. Using this application is not difficult, the user will only be directed to create an email and password so that he is registered as a member in this travel application and directed where the user wants to go. The process is also fast without having to wait long and we can set the day, date, or month when we want to order it. On the day of departure, we will only show proof that we have booked tickets in advance so that they can be checked directly on our destination computer, be it the terminal, port, or airport that we ordered on our cellphone